Caracterizacao edafo-climatica do Estado de Minas Gerais para a cultura da Cana-de-acucar - Koffler, N. F.; Coelho, M. B.; Weber, H.; Garcia, E. B. (My University, 1990)
An ecological zoning originates seven regional units according to the main limitations to sugar cane culture. -from English summary
Edapho-climatic characterization of the State of Minas Gerais (Brazil) for sugarcane growing
Keywords: climate; crop suitability study; ecological zoning; soil; soils; sugar cane; sugarcane; Brazil, Minas Gerais; Saccharum officinarum